O-1 Life's hard and then you die: PhD exploring end of life priorities within the UK homeless population. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Webb, Wendy Ann; Mitchell, Theresa; Snelling, Paul; Nyatanga, Brian
Abstract : Background: People experiencing homelessness often die young, of treatable diseases. They are dying on the streets and in hostels without adequate support. While there is ample literature surrounding the barriers to appropriate end of life care (Klop et al ., 2018), the end of life priorities of people experiencing homelessness in the United Kingdom (UK) remain poorly understood (Care Quality Commission, 2017). This study aims to bridge the gap in knowledge. The research question: The central question of this study is: 'What matters most to people experiencing homelessness in the UK as they consider their own end of life?' Aim of study: The aim of this interpretive phenomenological study is to explore the end of life concerns, fears, preferences and priorities of a sample of people experiencing homelessness in the UK. Methodology: This qualitative PhD project is a phenomenological study underpinned by the philosophy of French phenomenologist, Maurice Merleau-Ponty. Data have been collected through semi-structured, audio-recorded, face-to-face interviews with 21 participants (people experiencing homelessness) across several UK counties. Data have been analysed iteratively using thematic analysis. Findings: Findings are reported as eight themes: Spiritual concerns; Practical concerns; Fear of needing care; Fear of being forgotten; Preference for dying suddenly; Preference for being somewhere comfortable where people know me; Prioritising autonomy and self-determination; Prioritising authenticity. Findings are interpreted using Merleau-Ponty's philosophy. Discussion: 'What matters most to people experiencing homelessness in the UK as they consider end of life?' When the answers to this important question are understood, the problem of people experiencing homelessness in the UK dying without adequate support and with very little dignity or choice can begin to be addressed.